Separation of xanthines in hydro‐organic and polar‐organic elution modes on a titania stationary phase. Issue 5 (10th January 2014) - Jaoudé, Maguy Abi; Lassalle, Yannick; Randon, Jérôme
<x xml:space="preserve">Abstract</x> Hydrophilic interaction LC was investigated in hydro‐organic and nonaqueous elution modes on a titania column by using a set of N‐methyl xanthines as neutral polar probes. To get information regarding the mechanisms that are behind the discrimination of these analytes in hydrophilic interaction, we focused our study on the type and amount of organic modifier as a critical yet rarely explored mobile phase parameter. Several alcohols such as methanol, ethanol, and isopropanol were studied as substitutes to acetonitrile in hydro‐organic elution mode. Compared to silica, the investigation of the eluotropic series of these alcohols on titania highlighted a different implication in the retention mechanism of the xanthine derivatives. At low amounts of protic solvents, the adsorption mainly characterized the retention of analytes on bare silica; whereas mixed interactions including adsorption and ligand exchange were identified on native titania. To investigate the peculiar behavior of alcohols on the metal oxide, methanol, ethanol, and ethylene glycol were tested in replacement of water in polar‐organic elution mode. Distinctive effects on the chromatographic retention and selectivity of xanthines were noticed for the dihydric alcohol, which was found to be a stronger eluting component than water on titania.